The Impact of Social Media on Communication Politeness: A Survey of Prospective Primary School Teacher Students - Julia, Julia; Kurnia, Dadang; Sudin, Ali (Universitas Pendidikan Indonesia, 2018)
The presence of social media in our daily life gives both its positive and negative impact to communication manners. This impact also occurs in schools’ environment or even in campus. This paper aims to analyze students’ politeness in communicating through the social media. The study was conducted by providing a survey to 147 students (ages between 19-24 years). The results of the study prove that communication through social media give an impact on students to be more eager to communicate with anyone. However, their communication politeness has decreased, as the survey shows that the ethics of communicating through social media are nor good or polite. Therefore, it can be concluded that the social media has influenced the communication politeness between students and students and between students and lecturers.